2015
DOI: 10.1016/j.gloplacha.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of global pollution and recent environmental change in Kamchatka, Russia

Abstract: Kamchatka is a remote, isolated and understudied area and is presumed to be pristine. Here we present the first high-resolution palaeolimnological investigation of the recent past. A short core representing the last 250 years was taken from Olive-backed Lake situated in central Kamchatka. Lead-210 dating revealed that sediment accumulation has increased at the site since the 1960s and may be related to greater rates of catchment erosion associated with wetter winters in the region. Mercury and spheroidal carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 73 publications
0
12
1
Order By: Relevance
“…Observations in Canada have shown that E. pedicellatum is sensitive to acidic precipitation (Maass & Yetman 2002). In Kamchatka, the level of air pollution is low in general, despite occasional volcanic activity, and detrimental levels of pollution were not found within local environments that could threaten E. pedicellatum populations (Jones et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Observations in Canada have shown that E. pedicellatum is sensitive to acidic precipitation (Maass & Yetman 2002). In Kamchatka, the level of air pollution is low in general, despite occasional volcanic activity, and detrimental levels of pollution were not found within local environments that could threaten E. pedicellatum populations (Jones et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We can dismiss significant impacts from the mining settlement 17 km NW of the lake because it was established only two years before core retrieval. Analyses of Hg in sediments of Lake Baikal (Gelety et al 2007) and other lakes (Jones et al 2015;Lamborg et al 2002) showed that Hg concentrations in sediments of remote natural lakes reflect variations in the Hg concentration in the atmosphere. In industrial areas, Hg adheres to aerosol particles and is transported over thousands of kilometers from its source for up to one year before being deposited (Lucotte et al 1995).…”
Section: Geochemical Impacts To the Lake Ecosystem At The Onset Of Inmentioning
confidence: 99%
“…Whereas atmospheric change acts mainly at a global scale, the impact of pollution occurs mainly at regional and local scales. Global influences on the environment can be recognized in pristine ecological systems that are not directly affected by local anthropogenic activities, such as in the vast boreal areas of the Northern Hemisphere (Jones et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In remote lakes, anthropogenic heavy metals are usually derived dominantly from atmospheric deposition. Hence sediment records from these lakes usually document atmospheric deposition changes in the past and thus often employed to reconstruct pollution histories (Catalan et al, 2013;Engels et al, 2018;Jones et al, 2015;Sarkar et al, 2015;Wan et al, 2016). In recent years, such kind investigations have been carried out in many lakes from relatively remote areas of China, such as the Tibetan Plateau, West China, the Yungui Plateau (e.g.…”
Section: Introductionmentioning
confidence: 99%